PENERAPAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN REPRESENTASI MATEMATIS SISWA SEKOLAH DASAR : STUDI LITERATUR - Rahmadani, Nuzul; Ali, Amna; Erwin Efendi Hutagalung; Ayatullah Muhammadin Al Fath (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the implementation of the Realistic Mathematics Education (RME) approach in improving elementary school students’ problem-solving and mathematical representation abilities. This research employs a literature review method by analyzing various relevant journal articles. The findings indicate that the RME approach enhances students’ problem-solving skills through a systematic thinking process, including understanding the problem, planning strategies, implementing solutions, and evaluating results. In addition, RME improves students’ mathematical representation abilities in various forms, such as visual, symbolic, verbal, and tabular or graphical representations. These two abilities are closely interconnected and mutually supportive in developing a more comprehensive understanding of mathematics. Therefore, the RME approach is considered effective and relevant in creating meaningful mathematics learning in elementary schools.